Penerapan Bimodal Stimulasi Sensori terhadap Penurunan Kapasitas Adaptif Intrakranial pada Pasien Stroke Hemoragik di RS Mardi Rahayu Kudus - Heni Kristiani; Sri Puguh Kristiyawati (NAJ Nursing Applied Journal, 2025)
Background: Hemorrhagic stroke is a critical condition caused by the rupture of cerebral blood vessels, which leads to intracranial bleeding, increased intracranial pressure (ICP), and decreased adaptive capacity of the brain. One of its main impacts is a significant disturbance of consciousness. Nurses have applied non-pharmacological approaches, such as bimodal sensory stimulation, as innovative interventions to stimulate neurological function and indirectly stabilize intracranial pressure. Objective: This study analyzed the implementation of bimodal sensory stimulation in improving intracranial adaptive capacity in patients with hemorrhagic stroke. Methods: This case study involved a patient with a hemorrhagic stroke and impaired consciousness in an intensive care unit. The intervention was conducted for three consecutive days by providing auditory stimuli (voices of family members and nurses) and gustatory stimuli (lemon) five times daily. Measurements included the Glasgow Coma Scale (GCS) and neurological response observations. Results: After receiving bimodal sensory stimulation therapy, the patient showed improved consciousness, as indicated by a consistent increase in GCS scores from 9 to 11 over the three days. The patient's responses to auditory and gustatory stimuli also improved, including mild motor movements, pupil reflexes, and simple interactions such as blinking or opening the eyes in response to sounds. Conclusion: Bimodal sensory stimulation effectively facilitated the recovery of consciousness and enhanced intracranial adaptive capacity in patients with hemorrhagic stroke. Nurses can integrate this intervention into evidence-based nursing practice in intensive care units with active family involvement.